Panchromatic imaging and modeling of SSTtau J042021+281349: A new prototypical edge-on protoplanetary disk. Issue Volume 8:Issue S299(2013) (6th January 2014) - Duchêne, G.; Stapelfeldt, K.; Isella, A.; Perrin, M.; Ménard, F.; Padgett, D.; Pinte, C.; Wolff, S.; Krist, J.; Ghez, A.; Konopacky, Q.
Abstract: We present new high-resolution observations and modeling of SSTtau J042021+ 281349, a 400 AU-radius edge-on protoplanetary disk. We have gathered visible and near-infrared scattered light images of the system with the Hubble Space Telescope and Keck adaptive optics system, as well as a 1.3 mm continuum map with CARMA. Compared to the well-known HH 30 disk, this new system is remarkable because of its spectacular bipolar jet and the high degree of lateral symmetry of the disk. Indeed, we argue that this system is a "cleaner" prototype for edge-on disks. In addition, the apparent achromaticity of dust properties (most notably the almost grey opacity law) from the visible to the near-infrared in this disk suggests that it is in an advanced stage of dust evolution.